Pengaruh Harga dan Word of Mouth terhadap Keputusan Pembelian Daging Babi pada Warung Andira Blahkiuh Kabupaten Badung (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine how the influence of design and brand image. The purpose of this study was to determine the partial and simultaneous influence of price and word of mouth on purchasing decisions of pork at Warung Andira Blahkiuh, Badung Regency. The method of collecting data in this study was carried out by means of interviews, documentation studies and questionnaires. Questionnaires were given to 100 respondents, to be further analyzed using multiple linear regression, determination, t test and F test. The results of this study are that price has a positive and significant effect on pork buying decisions at Warung Andira Blahkiuh. This means that the better the application of prices, the higher the purchasing decision of pork at Warung Andira Blahkiuh. Word of mouth has a positive and significant effect on pork purchasing decisions at Warung Andira Blahkiuh. This means that the better the word of mouth, the higher the decision to buy pork at Warung Andira Blahkiuh. Price and word of mouth have a positive and significant effect on pork purchasing decisions at Warung Andira Blahkiuh. This means that the better the word of mouth, the higher the purchasing decision at Warung Andira Blahkiuh.